Room-temperature large magnetocaloric effect in perovskites (Lai.xNdx)o.vSro.3Mn03 - Luong, Nguyen Hoang; Mai Phuong, Nguyen Thi; Hien, Phung Thu; Nhat, Hoang Nam; Hoang, Luc Huy; Chau, Nguyen; Hai, Nguyen Hoang (VNU Journal of Science: Mathematics - Physics; Vol 24 No 1, 2008)
Abstract